2009
DOI: 10.1007/s10725-009-9365-0
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid (ABA) inhibition of lateral root formation involves endogenous ABA biosynthesis in Arachis hypogaea L.

Abstract: ABA has been found to play a significant role in post-embryonic developmental in peanut seedlings. The results from the current study indicate that in the presence of exogenous 10 lmol l -1 ABA, lateral roots (LRs) number decreased and seedling development was delayed. This effect was eliminated by 25 lmol l -1 naproxen, an inhibitor of ABA biosynthesis. The Arabidopsis mutant deficient in ABA biosynthesis, nced3, displays a phenotype with more and longer LRs. We found that ABA decreased rootbranching in peanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…Barrero et al (2006) provided further evidence that strong induction of AtNCED3 gene by ABA occurred through both ABA-dependent and ABA-independent pathways in Arabidopsis. We recently showed that the expression of AhNCED1 gene in peanut plants was upregulated by exogenous ABA treatment (Wan and Li, 2006;Guo et al, 2009). In the present study, imbibition of exogenous ABA by peanut seeds led to a significant increase in the levels of AhNCED1 gene transcript ( Figure 2A) and ABA ( Figure 2B), and conversely imbibition of naproxen significantly decreased the levels of endogenous ABA ( Figure 2B) and AhNCED1 gene transcript (Figure 2A).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Barrero et al (2006) provided further evidence that strong induction of AtNCED3 gene by ABA occurred through both ABA-dependent and ABA-independent pathways in Arabidopsis. We recently showed that the expression of AhNCED1 gene in peanut plants was upregulated by exogenous ABA treatment (Wan and Li, 2006;Guo et al, 2009). In the present study, imbibition of exogenous ABA by peanut seeds led to a significant increase in the levels of AhNCED1 gene transcript ( Figure 2A) and ABA ( Figure 2B), and conversely imbibition of naproxen significantly decreased the levels of endogenous ABA ( Figure 2B) and AhNCED1 gene transcript (Figure 2A).…”
Section: Discussionsupporting
confidence: 62%
“…However, the feedback regulation of ABA biosynthesis in higher plants needs to be investigated further. We found that ABA inhibited lateral root development of peanut plants by up-regulation of AhNCED1 gene causing accumulation of endogenous ABA (Guo et al, 2009). Szepesi et al (2009) suggested a positive feedback regulation of ABA synthesis by salicylic acidHu et al 1579 induced ABA accumulation in tomato plants, and Barrero et al (2006) showed that accumulated ABA levels exerted a positive feedback on its own biosynthetic pathway in Arabidopsis, inspite of some earlier reports where no feedback regulation was found in ABA biosynthesis in cowpea (Iuchi et al, 2000) and tomato (Thompson et al, 2000).…”
mentioning
confidence: 87%
“…Response to salinity stress, unlike osmotic and nitrogen stress, utilize both ABA-dependent and -independent pathways acting through ROS intermediates (Guo et al 2009;Lim et al 2010;Mahajan and Tuteja 2005;Zhu 2002). The air12 seedling response to KCl differed than that of either nitrate or mannitol and may proceed through a pathway not mediated by ABA.…”
Section: Discussion Germination and Root Growthmentioning
confidence: 99%
“…Plant cells capitalize on the ability of hydrogen peroxide, a relatively stable ROS, to freely diffuse across the plasma membrane, acting as a membrane diffusible signaling molecule (Levine et al 1994) to control root development (Joo et al 2001;Guo et al 2009 Auxin has a promotive effect on ROS production, stimulating cell elongation in maize coleoptiles (Rodriguez et al 2002) and cell elongation requires an extracellular pool of ROS (Schopfer et al 2002). As the major enzyme complex involved in the production of extracellular ROS, NOX may be the central component required for cell elongation.…”
Section: Involvement Of Ros During Auxin and Aba-induced Lateral Growthmentioning
confidence: 99%
“…Previously, we investigated the effect of ABA on LR formation in peanut seedlings and demonstrated that ABA decreased root branching in a dose-dependent manner. Interestingly, naproxen, an ABA biosynthesis inhibitor, induced an increase in the number and length of visible LR (Guo et al, 2009). In the presence of 5 M naphthalene acetic acid (NAA), more LR formation (e.g.…”
Section: Introductionmentioning
confidence: 99%